Acceptability of testing for anorectal sexually transmitted infections and self-collected anal swabs in female sex workers, men who have sex with men and transgender women in Papua New Guinea - Stephen Bell; Johanna Wapling; Sophie Ase; Ruthy Boli-Neo; Andrew J. Vallely; John M. Kaldor; Claire E. Nightingale; Angela Kelly-Hanku (BMC, 2018)
Abstract Background Papua New Guinea (PNG) has some of the highest prevalence of urogenital sexually transmitted infections (STIs) in Pacific Asia, but to date, anorectal STI prevalence data do not exist, and diagnosis of anorectal STIs does not occur. The purpose of this study was to document the acceptability of anorectal STI testing and self-collection of anorectal swabs for testing among populations at risk of anorectal STIs, in advance of a large bio-behavioural survey during which this approach to specimen collection was planned among key populations in PNG. Methods Four focus groups were conducted, collecting data from a purposive sample of 35 members of two civil society groups representing female sex workers, men who have sex with men and transgender women in Port Moresby and Goroka. Results All participants were in favour of anorectal STI testing in PNG. Reasons given for willingness to undertake anorectal STI testing included that anal sex is practised; that anorectal STIs are not perceived to exist; there are self-reported experiences of anorectal symptoms indicative of anorectal STIs; that anorectal STI testing will enhance personal health; and that anorectal STI testing is not currently available in PNG. All participants were confident they could obtain self-collected specimens, although several stated that support from trained health workers should be available for community members who may not feel comfortable with self-collection. Conclusions This qualitative research is the first study of acceptability of anorectal STI testing and specimen self-collection procedures in PNG, and Pacific Asia more broadly. Our qualitative findings show support for anorectal STI testing including the use of self-collected swabs among key populations in PNG. Study findings informed the inclusion of anorectal STI testing in a large bio-behavioural survey to be used to estimate anorectal STI prevalence among key populations in PNG for the first time.